NEED ANALYSIS OF FOLKLOR TEXTBOOKS BASED ON PROJECT BASED LEARNING FOR STUDENTS IN HIGHER EDUCATION - Wirasty.B, Rini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
This research aims to analyze the need for developing folklore textbooks based on Project Based Learning (PBL) for students in tertiary institutions. The research method used is a descriptive qualitative approach, with data collection techniques through interviews, class observations and documentation studies. This research involved lecturers and students taking folklore courses at several universities to find out their challenges, needs and hopes regarding folklore learning. The research results show that there is a need for more applicable and contextual textbooks, which integrate folklore theory with practical experience, such as field research and creating culture-based projects. In addition, the PBL approach is expected to increase students' active involvement in the learning process, develop research, collaboration and problem solving skills. Based on these findings, this research produces a concept for developing a PBL-based folklore textbook designed to facilitate more interactive and meaningful learning. It is hoped that the textbook being developed can enrich students' understanding of folklore and provide practical skills that are relevant to the professional world.